Comparison of circuit patency and exchange rates between the original and generic versions of nafamostat mesylate in critically ill adults receiving continuous renal replacement therapy - Sujung Heo; Yanghyeon Kim; Nagyeom Lee; Ye Na Kim; Ho Sik Shin; Yeonsoon Jung; Hark Rim (Kosin Medical Journal, 2023)
Background Nafamostat mesylate is widely used as an anticoagulant in continuous renal replacement therapy (CRRT). The generic versions of nafamostat mesylate have identical main components to the original product. However, it is questionable whether the generic versions have the same efficacy as the original. Therefore, we compared the circuit patency and exchange rates of the original nafamostat mesylate and a generic version to determine which is more efficient as an anticoagulant in CRRT. Methods This retrospective study enrolled 1,255 patients hospitalized to receive CRRT who received the original version of nafamostat mesylate or a generic version between January 2010 and July 2018. We evaluated the filter lifespan, number of filters used per day, mean blood flow, and transmembrane pressure (TMP). Results The mean filter lifespan was 36.3±15.1 hours in the original product group and 22.2±16.2 hours in the generic product group, which was not a statistically significant difference (p=0.060). The mean TMP was 62.2±47.3 mmHg in the original product group and 74.5±45.6 mmHg in the generic product group (p=0.045). Conclusions This retrospective study suggests no meaningful difference in filter lifespan between the original and generic versions of nafamostat mesylate. However, TMP was lower in the original product group than in the generic product group.